SISTEM INFORMASI GEOGRAFIS PERSEBARAN PETERNAKAN DI WILAYAH PROVINSI RIAU - Muhammad Alif Farhan; Erzi Hidayat (Politeknik Negeri Bengkalis, 2023)
The Riau Provincial Livestock and Animal Health Office (DISTANAK) is a department that aims to manage livestock and animal health in the Riau Province area. Currently, distanak Riau is conducting data collection on livestock groups using conventional methods with file document storage. This has led to the inability of distanak to digitally visualize the distribution of livestock in the Riau area. Additionally, distanak does not have a system to measure the distance from livestock points to densely populated areas to prevent conflicts with the community arising from environmental disturbances. this research aims to develop a Geographic Information System (GIS) for the distribution of livestock in the Riau region. The prototype method is used to obtain a system that meets user requirements. The development process involves three iterations. The system is tested using two methods: black box testing and user acceptance testing. From the black box testing, which includes 37 test cases, it is found that the Geographic Information System for livestock distribution is functional. Similarly, the user acceptance testing conducted by distanak administrators and staff confirms that the system's functionalities are appropriate, ensuring that all user requirements are met and accepted overall.